Oxylipin patterns in human colon adenomas. (April 2021) - Schmöcker, Christoph; Gottschall, Heike; Rund, Katharina M.; Kutzner, Laura; Nolte, Fabian; Ostermann, Annika I.; Hartmann, Dirk; Schebb, Nils Helge; Weylandt, Karsten H.
Highlights: PGE2 levels in human adenoma tissue are unchanged compared to healthy colon tissue. Human colon adenoma tissue shows significantly lower levels of most COX-derived eicosanoids as compared to healthy tissue. 5- and 12-LOX metabolites are increased in adenoma tissue and may be an additional target for CRC chemoprevention. Aspirin treatment tends to further suppress eicosanoid formation in colon adenoma tissue. Abstract: Objective: Cyclooxygenase (COX)-derived prostaglandin E2 (PGE2 ) is an important lipid mediator in colorectal carcinoma (CRC) pathogenesis. Other lipid mediators derived from lipoxygenases (LOX) have also been implicated in neoplastic processes in the colon. In this study we aimed to characterize lipid mediators, so called oxylipins, in human colon adenomatous polyps. Design: We quantified oxylipins in healthy colon tissue and colorectal adenoma tissue procured during routine colonoscopy examinations. Lipid metabolite profiles were analyzed by liquid chromatography-tandem mass spectrometry. Results: Adenoma tissue showed a distinct prostaglandin profile as compared to normal colon mucosa. Interestingly, PGE2 was not higher in adenoma tissue as compared to normal mucosa. In contrast, we found significantly lower levels of prostaglandin D2, prostaglandin J2, and prostaglandin D1 in adenoma tissue. Furthermore, levels of 5-LOX and 12-LOX pathway products were clearly increased in adenoma biopsy samples. We also investigated the effect of aspirin treatment on prostaglandin profiles in adenoma tissue in a subset of patients and found a trend towards decreased prostaglandin levels in response to aspirin. Conclusion: The human data presented here show specific changes of oxylipin profiles in colon adenoma tissue with decreased prostaglandin D2 levels as well as increased 5- and 12-LOX metabolites.